Economic benefits of sustainable agricultural production : the case of integrated pest management in cabbage production. - Shamsudin, Mad Nasir; Mohd Amir, Hairuddin; Radam, Alias (Thai Society of Higher Eduction Institutes on Environment, 2010)
Environmental protection is a basic element of sustainable agricultural development. Agricultural production practices,however, can cause negative externalities. One main concern of the externality is the negative effects of pesticide use. This has motivated the application of Integrated Pest Management (IPM) program. This study attempts to evaluate the economic benefits of IPM to address the widespread misuse of pesticides in cabbage production. IPM application in cabbage production includes initiatives on the optimal use of pesticides, complementary weed control strategies, and alternative cultural and biological controls. Results of this study showed that the programme would generate economic benefits which include improvements in water quality, food safety, pesticide application safety, and long term sustainability of pest management systems. Thus there is justification for public investment of resources in training and educational programs to increase awareness about IPM and promote IPM adoption.